2019
DOI: 10.1017/ice.2019.63
|View full text |Cite
|
Sign up to set email alerts
|

Test stewardship, frequency and fidelity: Impact on reported hospital-onset Clostridioides difficile

Abstract: We assessed the impact of an embedded electronic medical record decision-support matrix (Cerner software system) for the reduction of hospital-onset Clostridioides difficile. A critical review of 3,124 patients highlighted excessive testing frequency in an academic medical center and demonstrated the impact of decision support following a testing fidelity algorithm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 5 publications
0
15
0
Order By: Relevance
“…7 Multiple recent studies have demonstrated that clinical decision support incorporated into the electronic health record (EHR) can aid in reducing inappropriate C. difficile testing and overall hospitalonset CDI rate. [8][9][10][11][12][13][14] However, additional research has noted that clinicians often disregard such guidance and rely instead on clinical judgement and personal beliefs about CDI. 10,15,16 We implemented a series of clinical decision support interventions in the EHR from January 2018 to July 2019 with the goal of increasing appropriateness of C. difficile testing across our 3-hospital health system.…”
mentioning
confidence: 99%
“…7 Multiple recent studies have demonstrated that clinical decision support incorporated into the electronic health record (EHR) can aid in reducing inappropriate C. difficile testing and overall hospitalonset CDI rate. [8][9][10][11][12][13][14] However, additional research has noted that clinicians often disregard such guidance and rely instead on clinical judgement and personal beliefs about CDI. 10,15,16 We implemented a series of clinical decision support interventions in the EHR from January 2018 to July 2019 with the goal of increasing appropriateness of C. difficile testing across our 3-hospital health system.…”
mentioning
confidence: 99%
“…This intervention led to a 27% decrease in raw numbers of C. difficile tests as previously reported. 17 In this study, testing rates (to account for monthly patient volumes) similarly decreased with the EMR decision support. HO-CDI-rate models adjusted for testing rates demonstrated a lessening effect of intervention 5 compared with unadjusted models, suggesting that the decrease in reported HO rates is driven by lower testing volume rather than by tangible infection prevention benefit.…”
Section: Discussionmentioning
confidence: 53%
“…Fidelity to an evidence-based testing protocol did improve after intervention 5, as previously reported. 17…”
Section: Resultsmentioning
confidence: 99%
“…A recent retrospective study demonstrated that an embedded electronic medical record decision-support matrix for ordering C. difficile testing resulted in a 27% reduction in total C. difficile testing, suggesting that electronic prompts are important in bolstering C. difficile diagnostic stewardship strategies. 30 Our study has several limitations, including potential shortcomings of the electronic health record (EHR) during the study periods. For example, documentation of CDI parameters, such as the number and consistency of stool (ie, Bristol stool type), was not consistently recorded and thus was not collected in this study.…”
Section: Discussionmentioning
confidence: 99%